Subcutaneous Splenosis of the Abdominal Wall: Report of a Case and Review of the Literature - Evangelia Papakonstantinou; Vasileios Kalles; Ioannis Papapanagiotou; Theodoros Piperos; Dimitrios Karakaxas; Vasileios Bonatsos; Konstantinos Tsoumakas; Filotheos Orfanos; Theodoros Mariolis-Sapsakos (Case Reports in Surgery)
Splenosis is a common benign condition that occurs after splenic rupture via trauma or surgery. The mechanism behind splenic cell autotransplantation begins with the splenic rupture, either from trauma or surgical removal. Splenosis is usually found incidentally and, unless symptomatic, surgical therapy is not indicated. Subcutaneous splenosis is an extremely rare form of splenosis, mostly observed in abdominal surgical scars. We report a case of subcutaneous splenosis, as well as a comprehensive review of the literature. In our case, a 43-year-old woman who had splenectomy after traumatic splenic rupture at the age of 7 years old presented for plastic reconstruction of her postoperative scar. Upon surgery, two asymptomatic subcutaneous nodules were incidentally discovered. The presence of splenic tissue was confirmed by the histological study. The nodules were not excised, as the patient was not symptomatic.